Brand and its Identity as a Source of Added Value for a Metropolitan Area - Florek, Magdalena; Janiszewska, Karolina (Studia Oeconomica Posnaniensia, 2015)
A brand is perceived as a combination of functional and emotional features which are of importance in the selection process and providing user satisfaction underlies a classic model of added value. The concept has also been applied with reference to place brands. This indicates that if an administrative unit intends to create added value for its stakeholders the authorities should manage the place with the target groups' needs and expectations in mind i.e. adopt a marketing concept targeted at brand building. At the same time metropolitan areas are becoming similar with respect to their functions and attributes. Therefore, it is their ability to create added value that may differentiate them and determine the target groups' preference. In this context a definition of the brand identity of the place is of key and strategic importance. It determines in a significant way the perception of the location and ultimately creates added value. It is worth emphasizing that, in the case of metropolitan areas, the process of creating added value involves the use of important assumptions about the relationships between the units of which the metropolitan areas consist. If done skilfully emphasized the relations may result in a synergy of added value.